The Perspectives Of Native Kansai Dialect Speakers Towards The Kansai Dialect And Standard Japanese - Muhammad Arsy Nur Raihan; Andy Bangkit Setiawan (International Forum of Researchers and Lecturers, 2023)
This research analyzes the Kansai dialect, Standard Japanese, and the perspectives of native Kansai dialect speakers towards both languages. The purpose of this study is to find out what native speakers of Kansai dialect feel about their dialect and their views on Standard Japanese. This research uses a qualitative method with a thematic analysis approach. The data for this study were gathered from comments on threads and questions posted on the jp.quora.com website. The researcher's conclusion is that native Kansai dialect speakers have a sense of pride in their language and do not hold any particular views towards Standard Japanese.